Model and Implementation of Robotic Arm Using Android. - rani, M. Sunitha; Valantina, G. Mary; Reddy, M. Harsha vardhan; Hrithik, S.; Shankar, Mani; Teja, K. Sai (Turkish Journal of Physiotherapy Rehabilitation, 2021)
In day-to-day life, technology is growing rapidly and helping human requirements. The proposed system is on embedded system which uses for human work easier using the robotic arm. Normally the traditional way of lifting goods and keep somewhere is needed, large place, and cost-effective. This system will easy to handle and don't require much effective equipment and place. The system uses the Arduino Nano microcontroller for controlling the robot arm depends on the input given by the user, the user will the commands using the android application. The android application sends commands to the robot wirelessly using Bluetooth technology. The Bluetooth module at the robot receives the commands from the android application. Depends on the input given robot moves, picks, carry, and place. The system robot moves in four-axis directions and using 5 servo motors.